2009
DOI: 10.3945/jn.108.098293
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Catechin Consumption Enhances Exercise-Induced Abdominal Fat Loss in Overweight and Obese Adults

Abstract: This study evaluated the influence of a green tea catechin beverage on body composition and fat distribution in overweight and obese adults during exercise-induced weight loss. Participants (n = 132 with 107 completers) were randomly assigned to receive a beverage containing approximately 625 mg of catechins with 39 mg caffeine or a control beverage (39 mg caffeine, no catechins) for 12 wk. Participants were asked to maintain constant energy intake and engage in >or=180 min/wk moderate intensity exercise, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
178
6
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(207 citation statements)
references
References 36 publications
13
178
6
10
Order By: Relevance
“…Some authors found reduction of cholesterol in mice (KIM et al, 2009;RICHARD et al, 2009), while others did not find any difference (FARDET et al, 2008;ZHENG et al, 2004). The controversy also exists in clinical studies showing beneficial (HSU et al, 2008;NAGAO;HASE;TOKIMITSU, 2007) or no effect on blood cholesterol (MAKI et al, 2009) after green tea supplementation. Since antioxidant agents such as green and white tea do affect quantitatively the circulating lipoproteins and cholesterol, it is not surprising that they did not affect blood concentration of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors found reduction of cholesterol in mice (KIM et al, 2009;RICHARD et al, 2009), while others did not find any difference (FARDET et al, 2008;ZHENG et al, 2004). The controversy also exists in clinical studies showing beneficial (HSU et al, 2008;NAGAO;HASE;TOKIMITSU, 2007) or no effect on blood cholesterol (MAKI et al, 2009) after green tea supplementation. Since antioxidant agents such as green and white tea do affect quantitatively the circulating lipoproteins and cholesterol, it is not surprising that they did not affect blood concentration of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it seems unlikely that the lack of effect seen here was due to low dose or short time of experimentation. Nonetheless, clinical studies with active or inactive obese individuals did not support the action of green tea improving glucose homeostasis (HSU et al, 2008;MAKI et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al (2010) investigated the influence of tea drinking on the waist circumference, and the results were that for overweight Chinese taking green tea polyphenol (caffeine <200 mg) 458-886 mg/d for 90 d, the body fat could be decreased. A trial involving 132 overweight or obese women over 12 weeks demonstrated a significant reduction in abdominal fat and subcutaneous abdominal fat area in the group that consumed green tea compared with the control group (Maki et al, 2009). Hursel et al (2011) indicated that both treatments of a mixture of catechins and caffeine and caffeine alone could increase energy expenditure.…”
Section: Prevention Of Metabolic Syndrome (Mets) and Cardiovascular Dmentioning
confidence: 99%